Integrated approaches to selection control, microstructural analysis, and reliability assessment for bare dies - Mei, Liang; Wu, Rongrong; Kang, Wenqian; Cao, Yang; Li, Ruiyuan (Frontiers in Materials, 2025)
Due to limitations of device size and weight and the demand for multi-functional, high precision, and highly reliable devices, bare dies have been adopted instead of packaged components. By using dies directly without packaging, costs are somewhat reduced. However, without packaging protection, higher requirements on quality and reliability are imposed on bare dies. Based on system reliability, a comprehensive assessment must be made based on factors such as selection control, structural management, functional performance, and environmental adaptability. A typical die was initially selected, based on the application reliability risk analysis for bare dies, reliability evaluation projects were designed, and the reliability evaluation scheme was confirmed. The functionality, performance, reliability, and adaptability of the bare die were evaluated. The practical results demonstrated that the integrated evaluation method can effectively avoid the use of components with quality risks or insufficient reliability, contributing to the goal of reducing costs while ensuring product quality and reliability.